PERMINTAAN AUDIT PADA KOPERASI SIMPAN PINJAM: BENTUK TRANSPARANSI DAN AKUNTABILITAS - Miranti Kartika Putri; Indira Januarti (JURNAL AKUNTANSI DAN AUDITING, 2020)
The objective of financial statement auditing is to ascertain whether the financial statements prepared by the cooperation have been prepared in accordance with the provisions of the presentation. However, the culture to audit the financial statements of the cooperation is still very low. Thus it is necessary to identify and analyze factors that affect the demand for audit service. This study has the objective to analyze the influence of financial factor (gearing ratio), non financial factors (the number of members and the size of cooperatives) to demand audit service on “Koperasi Simpan Pinjam” at Central Java province level. The dependent variable used is dummy (nominal). Hypothesis was tested using logistic regression. Total sample of 130 units of “Koperasi Simpan Pinjam”, samples that can be processed and used only 93 units. The results of this study indicate that the variable number of members and the size of cooperative have positive effect on the demand for audit service, while variable gearing ratio do not influence the demand for audit service in the “Koperasi Simpan Pinjam”.